2016
DOI: 10.1111/bcpt.12662
|View full text |Cite
|
Sign up to set email alerts
|

Oesophageal Obstruction from a Pharmacobezoar Resulting in Death

Abstract: Formation of an intestinal pharmacobezoar is a rare condition. It may form after intake of various oral pharmaceutical preparations of drugs, both as a result of an acute overdose and through chronic use of therapeutic doses of a drug. We report a case with a patient presenting with an oesophageal pharmacobezoar and complete obstruction of the oesophagus and severe toxic symptoms and death related to oral ingestion of multiple drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…To our knowledge, 2 other cases have been reported in the literature involving the use of postmortem imaging in characterizing a bezoar. The first is from Mortensen et al 36 in which an 84-year-old man died of a pharmacobezoar. The authors stated that the PMCT scan identified tablet residues within his stomach.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, 2 other cases have been reported in the literature involving the use of postmortem imaging in characterizing a bezoar. The first is from Mortensen et al 36 in which an 84-year-old man died of a pharmacobezoar. The authors stated that the PMCT scan identified tablet residues within his stomach.…”
Section: Discussionmentioning
confidence: 99%
“…Other similar cases have been published, involving a wide range of medications. 8,12,14,16,17,20,22 Another important point must also be taken into consideration to explain these toxicokinetic alterations. Indeed, several of these reported cases involved ER or SR formulations.…”
Section: Discussionmentioning
confidence: 99%
“…Seventeen publications describing 19 cases of pharmacobezoar-related fatalities have been published between 1939 and 2021. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Decedents' mean age was 47.6 years (0.8-79). The male/female ratio was 13:6.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…At pH 3.5 or 6.5, ASA's intestinal absorption is higher than the gastric absorption of the compound. The stomach does not absorb ASA at pH 6.5 [11,12]. ASA elimination happens throughout dual pathways via the invention of salicyluric acid and salicyl phenolic glucuronide.…”
Section: Figure1 Mechanism Of Action Of Aspirinmentioning
confidence: 99%